2015
DOI: 10.1075/lia.6.1.01edm
|View full text |Cite
|
Sign up to set email alerts
|

What the present can tell us about the future

Abstract: This investigation studies the second language (L2) development of variable future-time expression in French. One hundred and eighteen nonnative speakers at four proficiency levels and 30 native speakers completed a written-contextualized task (WCT), a language-proficiency test and a background questionnaire. The verb form (inflectional future, periphrastic future, and present) selected for each item on the WCT was coded for three independent linguistic factors: presence of a lexical temporal indicator, tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For instance, concerning adverbial specification, the presence of a temporal adverbial favoured the occurrence of the futurate present among Canadian immersion students (Mougeon et al, 2010;Nadasdi et al, 2003), Irish studyabroad learners (Regan et al, 2009), adult Anglo-Montrealers (Blondeau et al, 2014), Level 3 study-abroad learners , and study-abroad learners with high proficiency (Gudmestad & Edmonds, 2016). However, this effect was not found for all study-abroad and foreign-language classroom learners reported on by Edmonds and Gudmestad (2015) and Gudmestad and Edmonds (2016). Third, with the exception of Anglo-Montrealers (Blondeau et al, 2014), no study has shown evidence of learners becoming fully targetlike with future-time expression.…”
Section: Ns Sociolinguistic Research Sociolinguistic Research On Futmentioning
confidence: 96%
“…For instance, concerning adverbial specification, the presence of a temporal adverbial favoured the occurrence of the futurate present among Canadian immersion students (Mougeon et al, 2010;Nadasdi et al, 2003), Irish studyabroad learners (Regan et al, 2009), adult Anglo-Montrealers (Blondeau et al, 2014), Level 3 study-abroad learners , and study-abroad learners with high proficiency (Gudmestad & Edmonds, 2016). However, this effect was not found for all study-abroad and foreign-language classroom learners reported on by Edmonds and Gudmestad (2015) and Gudmestad and Edmonds (2016). Third, with the exception of Anglo-Montrealers (Blondeau et al, 2014), no study has shown evidence of learners becoming fully targetlike with future-time expression.…”
Section: Ns Sociolinguistic Research Sociolinguistic Research On Futmentioning
confidence: 96%
“…At lower proficiency level, learners have been found to make a limited use of these periphrastic forms (Ayoun 2014;Bartning and Schlyter 2004;Edmonds and Gudmestad 2015;Howard 2012;Michot and Pierrard 2017). Their use seems to develop with L2 proficiency, especially in an immersion context, as a result of exposure to French native input.…”
Section: Second Language Acquisition Of Aller + Vmentioning
confidence: 99%
“…As a clear instance of the spatio-temporal metaphor, we examine the use of aller + V forms in the oral production of native speakers of French and English L2 learners of French. Studies on the acquisition of the future have shown a limited use of this periphrastic form, particularly at lower proficiency level (Ayoun 2014; Bartning and Schlyter 2004;Edmonds and Gudmestad 2015;Michot and Pierrard 2017) and in an instructed context (Howard 2012). Their use seems to develop with L2 proficiency, especially in an immersion context, as a result of exposure to French native input.…”
Section: Introductionmentioning
confidence: 99%